PERAN FUNGI MIKORIZA ARBUSKULA (FMA) DAN ASAM HUMAT TERHADAP PERTUMBUHAN BALSA (Ochroma bicolor Rowlee.) PADA TANAH TERKONTAMINASI TIMBAL (Pb) - Fatimah Nur Istiqomah; Sri Wilarso Budi; Arum Sekar Wulandari (Graduate School Bogor Agricultural University (SPs IPB), 2017)
The aims of this research were to analyze the role of arbuscular mycorrhizal fungi (AMF) and humid acid toward balsa (Ochroma bicolor Rowlee.) growth on soil contaminated by lead and to analyze Pb accumulation in balsa. This study used a split split plot design. The main plot was AMF with 5 levels; without AMF (A0), AMF from secondary forest (A1), AMF from rubber natural forest (A2), AMF from oil palm plantations (A3), and AMF from rubber plantations (A4). The subplot was humic acid with 2 levels; no humic acid (B0) and 100 mL humic acid (B1). The sub subplot was Pb with 3 levels; 0 ppm Pb (C0), 500 ppm Pb (C1), and 750 ppm Pb (C2). The role of AMF and humic acid was more effective on the soil with 0 ppm of Pb than at 500 ppm of Pb and 750 ppm of Pb. AMF from rubber natural forest was the most effective AMF to increase diameter, root dry weight and shoot dry weight. Humic acid was able to increase the growth of height of 22.87% and diameter of 24.86% better than no humic acid. Pb accumulation in the entire plant tissue was more than 1000 ppm. It inhibited the growth of balsa seedlings and causing dead in 17.52% plant.